Capnocytophaga catalasegens sp. nov., isolated from feline oral cavities - Suzuki, Michio; Imaoka, Koichi; Kimura, Masanobu; Morikawa, Shigeru; Maeda, Ken (International journal of systematic and evolutionary microbiology, 2023)
Three bacterial strains, KC07075, KC07079 and KC07084 T , were isolated from the oral cavity of cats in 2007 in Japan. These strains were Gram-negative rods, exhibited gliding motility, grew in air with 5 % CO 2 , and showed oxidase activity, but not catalase activity. The 16S rRNA gene sequences of the three strains were 100 % identical. The 16S rRNA gene sequence of strain KC07084 T showed 92.1 and 91.9% identity to the type strains of Capnocytophaga canis and Capnocytophaga felis , respectively, and showed 89.3–91.6% identity to other Capnocytophaga species. The major cellular fatty acids of strain KC07084 T were iso-C 15 : 0 (58.4 %) and summed feature 11 (13.1 %). The G+C content of DNA from strain KC07084 T was 33.7 mol%, and the genome size was 2.92 Mbp. Strains KC07075, KC07079 and KC07084 T showed digital DNA–DNA hybridization values (dDDH) values of 99.9 % and average nucleotide identity (ANI) values of 99.98 % with each other, strain KC07084 T had dDDH values of 18.7–28.2 % and ANI values of 67.12–72.30 % to the type strains of other Capnocytophaga species. All known species of the genus Capnocytophaga inhabiting the oral cavity of dogs and cats have catalase activity, but the three strains, including type strain KC07084 T , lacked catalase activity. These results of the phylogenetic analysis of the 16S rRNA gene sequence, biochemical characteristics, and dDDH and ANI values suggest that strain KC07084 T represents a novel species. We propose the name Capnocytophaga catalasegens sp. nov., with KC07084 T as the type strain (=JCM 32682 T =DSM 107252 T ).